Primary care randomised controlled trial of a tailored interactive website for the self-management of respiratory infections (Internet Doctor). Issue 4 (20th April 2016) - Little, Paul; Stuart, Beth; Andreou, Panayiota; McDermott, Lisa; Joseph, Judith; Mullee, Mark; Moore, Mike; Broomfield, Sue; Thomas, Tammy; Yardley, Lucy
Abstract : Objective: To assess an internet-delivered intervention providing advice to manage respiratory tract infections (RTIs). Design: Open pragmatic parallel group randomised controlled trial. Setting: Primary care in UK. Participants: Adults (aged ≥18) registered with general practitioners, recruited by postal invitation. Intervention: Patients were randomised with computer-generated random numbers to access the intervention website (intervention) or not (control). The intervention tailored advice about the diagnosis, natural history, symptom management (particularly paracetamol/ibuprofen use) and when to seek further help. Outcomes: Primary: National Health Service (NHS) contacts for those reporting RTIs from monthly online questionnaires for 20 weeks. Secondary: hospitalisations; symptom duration/severity. Results: 3044 participants were recruited. 852 in the intervention group and 920 in the control group reported 1 or more RTIs, among whom there was a modest increase in NHS direct contacts in the intervention group (intervention 37/1574 (2.4%) versus control 20/1661 (1.2%); multivariate risk ratio (RR) 2.25 (95% CI 1.00 to 5.07, p=0.048)). Conversely, reduced contact with doctors occurred (239/1574 (15.2%) vs 304/1664 (18.3%); RR 0.71, 0.52 to 0.98, p=0.037). Reduction in contacts occurred despite slightly longer illness duration (11.3 days vs 10.7 days, respectively; multivariate estimate 0.60 days longer (−0.15 to 1.36, p=0.118) and more days of illness rated moderately bad or worse illness (0.52 days; 0.06 to 0.97, p=0.026). The estimate of slower symptom resolution in the intervention group was attenuated when controlling for whether individuals had used web pages which advocated ibuprofen use (length of illness 0.22 days, −0.51 to 0.95, p=0.551; moderately bad or worse symptoms 0.36 days, −0.08 to 0.80, p=0.105). There was no evidence of increased hospitalisations (risk ratio 0.25; 0.05 to 1.12; p=0.069). Conclusions: An internet-delivered intervention for the self-management of RTIs modifies help-seeking behaviour, and does not result in more hospital admissions due to delayed help seeking. Advising the use of ibuprofen may not be helpful. Trial registration number: ISRCTN91518452.